Before dan After: Kemampuan Siswa Kelas V Setelah Belajar dengan Menggunakan Pendekatan Realistik Matematika - Hening Windria; Stevanus Budi Waluya; Scolastika Mariani (Departement of Mathematics Education, 2023)
Data has been an integrated part of daily life and it is important for students to be able to read data in its many representations. Therefore, there is a need for suitable teaching and learning approach to support students in learning how to read data, such as Realistic Mathematics Education (RME). The aim of this study is to discover whether RME is effective enough in supporting students by comparing students’ ability in reading data before and after the learning process. The data in this study was analyzed from the pretest and posttest result of 28 fifth grader of Jebed 3 Primary School in Pemalang, Central java. The data was analyzed using descriptive statistics, paired-sample t test, Cohen’s d effect size, and also normalized change. The study found that RME lesson can support students to be able to read data. Most students have the ability to read the data, but several students still have difficulties in making comparison and making further calculation to read between the data. Additionally, some students also had difficulty in perceiving the symbols representation in pictogram, and also in calculate numbers.